Penangguhan Eksekusi Terhadap Perkaran Kasasi Nomor 517 K/PDT/2022 Karena Adanya Uoaya Peninjauan Kembali Pada Mahkamah Agung Republik Indonesia - Yunimar, Yunimar; Arianti, Mesi (Normative Jurnal Ilmiah Hukum, 2025)
Legal remedies for a request for judicial review in principle do not suspend the implementation of the decision. Article 66 paragraph (2) of Law Number 14 of 1985 concerning the Supreme Court states "A request for review does not suspend or stop the implementation of a court decision", the principle regulated in this article is that the implementation of a court decision does not allow exceptions (uitzondering) to a decision or particular case. In the case that the author researched, namely cassation case number 517/K/Pdt/2020, the Chairman of the Padang Panjang Class II District Court postponed the execution on the grounds that there was a Request for Judicial Review submitted by the respondent to the execution. The problem formulation in this journal is: 1. What are the considerations of the Chairman of the Padang Panjang Class II District Court in determining the suspension of execution in cassation case No. 517/K/Pdt/2020 due to the Judicial Review efforts at the Class II District Court of Padang Panjang, 2. What is the legal analysis of the considerations of the Chairman of the Class II District Court of Padang Panjang in determining the suspension of execution for cassation case No. 517 K/Pdt/2022 due to a review effort at the Padang Panjang Class II District Court. The author conducted research using a normative juridical approach, the nature of the research is descriptive. Data collection techniques through literature study are then processed through editing and coding processes and analyzed qualitatively.